2019
DOI: 10.1590/abd1806-4841.20198203
|View full text |Cite|
|
Sign up to set email alerts
|

Adult female acne: a guide to clinical practice

Abstract: BackgroundAcne in women is often associated with anxiety and depression, and may persist from adolescence as well as manifest for the first time in adulthood. Genetic and hormonal factors contribute to its etiopathogenesis, and maintenance treatment is required, usually for years, due to its clinical evolution.ObjectiveTo develop a guide for the clinical practice of adult female acne.MethodsA team of five experts with extensive experience in acne conducted a literature review of the main scientific evidence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
145
0
32

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(177 citation statements)
references
References 111 publications
0
145
0
32
Order By: Relevance
“…The “late onset” subtype appears for the first time after the age of 25 years. A third subtype is “recurrent acne” which occurs in adolescence and improves only to reappear after 25 years of age . Hormonal dysfunction, genetics, cosmetics use, diet, smoking, and stress are implicated as a trigger in adult female acne .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The “late onset” subtype appears for the first time after the age of 25 years. A third subtype is “recurrent acne” which occurs in adolescence and improves only to reappear after 25 years of age . Hormonal dysfunction, genetics, cosmetics use, diet, smoking, and stress are implicated as a trigger in adult female acne .…”
Section: Introductionmentioning
confidence: 99%
“…A third subtype is "recurrent acne" which occurs in adolescence and improves only to reappear after 25 years of age. 2 Hormonal dysfunction, genetics, cosmetics use, diet, smoking, and stress are implicated as a trigger in adult female acne. 3 Though some authors feel that the role of androgens in adult female acne is tenuous, clinical signs of hyperandrogenism (HA) like hirsutism, androgenetic alopecia, and seborrhea are routinely reported across studies even though corroborative biochemical hyperandrogenemia is not consistently seen.…”
Section: Introductionmentioning
confidence: 99%
“…Along with acne, having acne scars is a risk factor for suicide and also may be linked to poor selfesteem, depression, anxiety, altered social interactions, body image alterations, embarrassment, anger, lowered academic performance, and unemployment [137]. Studies have also shown that the psychological impact of acne appears to affect more females than males [35]. Facial appearance has an important role in self-perception, as well as in the interaction with others; face lesions cause a significant impact in women's quality of life [147].…”
Section: Psychological Impact Of Avmentioning
confidence: 99%
“…Studies suggested that AEs at the application site occurred more often in Japanese patients than Western patients, most of the AEs were mild [172], [177]. It is most effective when used in combination with other acne vulgaris therapies [35]. BP is a bactericidal agent.…”
Section: Benzoyl Peroxidementioning
confidence: 99%
“…Currently, treatment of AFA often includes adapalene with benzoyl peroxide, which is associated with skin irritation and does not address the Malassesia dysbiosis. Ketoconazole (KTZ) cream, one of the commonly used imidazole antifungal drugs, with anti‐inflammatory effect and antiandrogenic activity, is an effective treatment for Malassezia ‐related skin disorders such as seborrheic dermatitis which is a frequent comorbidity with acne .…”
Section: Introductionmentioning
confidence: 99%